Lidless - Cowhig, Frances Ya-Chu, 1983- (Yale drama series., 2010)
"In the fifteen years since Alice served in the U.S. Army as an interrogator at Guantánamo Bay, she has successfully reinvented herself and suppressed all memories of her prior life, mostly through the aid of pharmaceuticals. She now lives contentedly, if not passionately, in Minnesota with her loving husband and precocious teenage daughter. That is, until Bashir, a Pakistani Muslim, shows up at Alice's flower shop and asks for part of her liver as compensation for the suffering he endured as one of her detainees. The request sets into motion a series of visceral and spiritual encounters among six characters whose lives will be forever connected and defined by a single act of inhumanity. This daring and beautiful play is at once searingly poetic and incisively political as it explores the nature of trauma, the conflicting eroticism and brutality of violence, and the blurry line between revenge and redemption."--Back cover.